Pengaruh Metode dan Motivasi dalam Prestasi Belajar Mata Kuliah Fisika Dasar - Halleyna Widyasari; Purni Munah Hartuti (SAP (Susunan Artikel Pendidikan), 2018)
Lectures are not simply about listening, reading and writing. Lectures need many things to achieve goals, including learning methods and learning motivation given by lecturers,such as the lecturer of Fundamental Physics. This subject needs a practice to help with the implementation of Physics and needs learning motivation that can encourage students to attend the lectures effectively. Some researches have been conducted on the effect of virtual physics simulation learning method and the provision of learning motivation on the Physics learning achievement. the research is conducted on first-level students of Informatics in a private University in Jakarta. The research uses an experimental treatment method by level 2x2. Through virtual simulation learning method, it is expected that the comprehension of Fundamental Physics materials can improve in line with student’s learning motivation. The result of the research shows that the virtual physics simulation learning method can be used as an alternative to Physics Practice and that the learning motivation has an effecton the Fundamental Physics learning achievement.